Acetylated and Methylated beta-Cyclodextrins as Viable Soluble Supports for the Synthesis of Short 2 '-Oligodeoxyribo-nucleotides in Solution - Molina AG; Kungurtsev V; Virta P; Lonnberg H (MDPI AG, 2022)
Novel soluble supports for oligonucleotide synthesis 11a-c have been prepared by immobilizing a 5'-O-protected 3'-O-(hex-5-ynoyl) thymidine (6 or 7) to peracetylated or permethylated 6-deoxy-6-azido-beta-cyclodextrins 10a or 10b by Cu(I)-promoted 1,3-dipolar cycloaddition. The applicability of the supports to oligonucleotide synthesis by the phosphoramidite strategy has been demonstrated by assembling a 3'-TTT-5' trimer from commercially available 5'-O-(4,4'-dimethoxytrityl) thymidine 3'-phosphoramidite. To simplify the coupling cycle, the 5'-O-(4,4'-dimethoxytrityl) protecting group has been replaced with an acetal that upon acidolytic removal yields volatile products. For this purpose, 5'-O-(1-methoxy-1-methylethyl)-protected 3'-(2-cyanoethyl-N, N-diisopropyl-phosphoramidite) s of thymidine (5a), N-4-benzoyl-2'-deoxycytidine (5b) and N-6-benzoyl-2'-deoxyadenosine (5c) have been synthesized and utilized in synthesis of a pentameric oligonucleotide 3'-TTCAT-5' on the permethylated cyclodextrin support 11c.